IMPLEMENTASI PROGRAM MAKASSAR TIDAK RANTASA (Studi Pengelolaan Sampah Berbasis Partisipasi) - Nuryadi Kadir (Jurnal Berita Sosial, 2018)
This study merupakaan review of the study of community empowerment in the context of urban phenomenon (urban) complex problems. Arrangement of cities that implicate the healthy lifestyle and clean, is an agenda in building collective awareness. Participation in waste management becomes a comprehensive performance framework for every urban, major city of Makassar. The community discourse in Makassar City related to waste management is a participatory public policy narrative. The Jargon